2003
DOI: 10.1097/01.lab.0000087591.29639.e3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NF2 and NF1 Tumor Suppressor Genes in Distinctive Gastrointestinal Nerve Sheath Tumors Traditionally Diagnosed as Benign Schwannomas: A Study of 20 Cases

Abstract: SUMMARY:A significant percentage of conventional schwannomas, whether sporadic or associated with neurofibromatosis 2 (NF2), show loss of heterozygosity (LOH) at NF2 and/or NF2 inactivating mutations. Similarly, a significant percentage of neurofibromas show LOH at NF1 and/or NF1 inactivating mutations. There are no molecular genetic data on gastrointestinal (GI) nerve sheath tumors traditionally diagnosed as benign schwannomas, rare neoplasms possibly derived from the schwannian elements dispersed between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 60 publications
2
39
0
Order By: Relevance
“…A strong association between these LOH and the degree of malignancy (2001 consensus criteria) was observed. This was expected, as several previous studies have shown associations between DNA alterations and GIST malignancy (2,6,17,21,22). As long-term follow-up data were available from our patients, the prognostic role of LOH could also be evaluated in this study.…”
Section: Discussionmentioning
confidence: 75%
“…A strong association between these LOH and the degree of malignancy (2001 consensus criteria) was observed. This was expected, as several previous studies have shown associations between DNA alterations and GIST malignancy (2,6,17,21,22). As long-term follow-up data were available from our patients, the prognostic role of LOH could also be evaluated in this study.…”
Section: Discussionmentioning
confidence: 75%
“…Of interest, intratumoral axons and perineurial cells were detected in GI schwannomas, supporting a neurofibroma-like histogenesis [31]. Moreover, the study by Lasota et al [32] has shown that loss of heterozygosity (LOH) at NF2 was rare in GI schwannomas (5%), and no NF2 mutations could be detected in 13 cases analyzed. Instead, LOH on 17q involving NF1 occurred frequently in GI schwannomas (50%), suggesting a distinct molecular pathogenesis that is more akin to that of plexiform neurofibroma [32].…”
Section: Discussionmentioning
confidence: 96%
“…Based on the evaluation of NFl and NF2 tumor suppressor genes, GI tract schwannoma is reckoned as an entity differing from the conventional form. 17 Valll, Na 1,2005 In contrast to earlier practice, samples from surgically resected gastrointestinal mesenchymal tumors have been mainly referred to the centers as GISTs or possible GISTs. Naturally, in places where it is not possible to perform ckit immunohistochemistry, or the primary tumor was operated on several years before, other diagnostic possibilities are more often raised.…”
Section: Pathology Oncology Researchmentioning
confidence: 99%